ANOMALOUS BEHAVIOR OF ELECTRONIC TRANSPORT PROPERTIES IN Cu-Sn LIQUID BINARY ALLOY - Ashwani Kumar; Durga P. Ojha
The Harrison’s First Principle technique in conjunction with the hard sphere technique of Ashcroft and Langreth has been used for the study of electrical resistivity, Knight shift, Fermi energy and density of states of Cu-Sn alloy. The alloy show the behavior of “rigid hard-sphere” model found for the first time in this alloy. Also, the Knight shift varies as a linear function of concentration supporting Kaeck’s assumption. The partial structure factors and hence resistivity shows anomalous behavior at a particular composition representing a dynatron type characteristic thereby producing a negative-resistance phenomenon in this alloy and hence making this material an important candidate for various industrial and commercial applications.
Keywords: Physics; Materials science